Poetic memory : allusion in the poetry of Callimachus and the Metamorphoses of Ovid - Tress, Heather van, 1966- (Mnemosyne, Supplements, 2004)
This book explores Callimachus' allusive practice in his Aetia prologue and Hymns 4, 5, and 6, and in Ovid's Metamorphoses . The study includes an overview of modern approaches to poetic allusion, a close (re-)examination of the lexical allusions in the Aetia's and Metamorphoses' prologues, extensive examinations of allusive techniques within selections of these works, the poets' use of \'signposting\' and \'authorization\' techniques, and the relationship between allusion and genre.